PERANCANGAN SISTEM INFORMASI INDEX PENYAKIT RAWAT INAP DI RSU PAKUWON SUMEDANG - Wulan Anggela; Yuda Syahidin; Irda Sari (Media Bina Ilmiah, 2022)
This research the medical record activities which has an influence on the quality medical services in hospitals are data processing, especially in making disease indexes and actions. In indexing activities at the Rumah Sakit Umum Pakuwon, processing inpatient disease index data has been computerized and integrated at SIMRS, but inputting disease index data is still done by pulling patient disease diagnosis data one by one into Microsoft Excel from SIMRS. So that the data input takes a long time and the patient's disease index cannot be processed as a whole into a report. This research aims to produce design of a disease index information system for inpatients using Microsoft Visual Studio 2010 as the software. The waterfall method was chosen to be the method applied in this research. In this research can result in system development for the patient disease index that already exists at the Rumah Sakit Umum Pakuwon into an information system that is more processed and more integrated with SIMRS, making it easier for officers to collect patient disease data as a whole, and making patient disease index reports can also be used done to the maximum.